Software Engineering Approaches for Scalable Applications - Muhammad Rizki Perdana (Asian Journal of Multidisciplinary Research, 2026)
Scalable applications have become essential in modern digital environments due to increasing user demands, large-scale data processing, and continuous technological advancements. This study aims to analyze software engineering approaches that support the development of scalable applications through a library research method. The study examines various academic sources related to microservices architecture, DevOps practices, cloud computing, database scalability, and software reliability. The findings indicate that microservices architecture provides flexibility and independent scalability compared to traditional monolithic systems. In addition, DevOps and CI/CD practices improve software delivery speed, operational efficiency, and collaboration among development teams. Cloud computing technologies also contribute significantly by offering flexible infrastructure and dynamic resource allocation. Furthermore, distributed databases and NoSQL systems enhance data management performance in large-scale applications. Overall, integrating modern software engineering approaches improves application scalability, reliability, maintainability, and adaptability in rapidly evolving digital ecosystems.